Fire Season - Weber, David 1952-; Lindskold, Jane M.; Dos Santos, Daniel (Riverdale, NY : Baen, 2012)
Stephanie Harrington and fellow ranger Karl Zivonik respond to the distress of Stephanie's alien friend Climbs Quickly and seek to protect the intelligent Treecat population on planet Sphinx from encroaching humanity.
"A Baen Books original"--T.p. verso.
Keywords: Human-animal relationships -- Fiction; Space colonies -- Fiction; Science fiction